HUBUNGAN WAKTU TUNGGU DENGAN TINGKAT KEPUASAN PASIEN DALAM MENDAPATKAN PELAYANAN KESEHATAN DI WILAYAH KERJA PUSKESMAS SIULAK MUKAI TAHUN 2023 - Pelani, Helman; Eliza, Eliza; Rahman, Waldi; Topis, Efrin (Ensiklopedia of Journal, 2024)
Abstract: Waiting Times is the length of time a patient waits for health services until they receive a prescription from a doctor. Waiting for a long time causes patient/customer dissatisfaction. It can be estimated that with high service quality it can prevent 2.5 million deaths due to negligence in service. The aim of the research was to determine the relationship between waiting time and the level of patient satisfaction in obtaining health services in the Siulak Mukai Community Health Center working area. The research used a non-experimental research design which was descriptive in nature, observations carried out on 1-5 August 2023 at the Siulak Mukai Community Health Center, with a sample size of 58 respondents. With waiting time and patient satisfaction variables. Data processing techniques use univariate and bivariate analysis with the SPSS application.The results of the study showed that the waiting time for respondents in the service was more at a waiting time of <40', namely 34 respondents (58.6%). Respondents' service satisfaction was more at the satisfaction level, namely 45 respondents (77.6%) Based on the results of statistical tests, there was pvalue=0.000, α<0.05 and OR 13,538. It can be concluded that there is a relationship between waiting time and the level of patient satisfaction in receiving health services at the Siulak Mukai health center. It is recommended for community health centers to improve the quality of services, especially regarding waiting times for health services provided at community health centers.Keywords: Waiting Time, Satisfaction, Service